Meiotic Behavior in Microsporocytes of Some Bananas in Thailand - Therdsak Thonnalak; Benchamas Silayoi; Yingyong Paisooksantivatana; Pradit Pongtongkam (Agriculture and Natural Resources, 2010)
Meiotic behavior was investigated in the microsporocytes of six wild bananas with AA and BB genomes and 46 cultivated bananas with AA, AAA, BBB, AAB and ABB genomes. All banana material was collected from the Pak Chong Research Station, Kasetsart University, Nakhon Ratchasima, Thailand. Most of the wild bananas showed normal synapses with a high chromosome pairing frequency of 11 bivalents per pollen mother cell (PMC). The cultivated bananas exhibited many variations in chromosome association at metaphase-I. Cultivars with the AA genome had more univalents than those of wild species with the same AA genome. Univalent, bivalent and trivalent occurrences were also common in all triploid cultivated bananas, but quadrivalents were very rare. The univalents were high in the AAB and ABB genomes, whereas trivalency was high in the AAA and BBB genomes. Micronuclei were observed in the tetrad of all cultivated bananas, but were very low in wild bananas. Many types of tetrad were shown in different orientation patterns at metaphase-II. The occurrence of the parallel disposition pattern was high, but the perpendicular and lineal disposition patterns were not common in any of the bananas.